2004
DOI: 10.2214/ajr.183.3.1830779
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Hemodynamic Effects of Pulmonary Angiography in Patients with Pulmonary Hypertension: 10-Year Single-Center Experience

Abstract: The complication rate of pulmonary angiography in patients with pulmonary hypertension is low. However, in severely ill patients with acute pulmonary hypertension, pulmonary angiography should be undertaken with extreme caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
0
18
0
3
Order By: Relevance
“…These numbers were lower than expected because patients with pulmonary hypertension are a high-risk population, and fatal complications of invasive procedures have been repeatedly reported in these patients (11)(12)(13)21,26,27). Earlier series from the 1980s and 1990s reported much higher complication rates.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These numbers were lower than expected because patients with pulmonary hypertension are a high-risk population, and fatal complications of invasive procedures have been repeatedly reported in these patients (11)(12)(13)21,26,27). Earlier series from the 1980s and 1990s reported much higher complication rates.…”
Section: Discussionmentioning
confidence: 84%
“…A series of 402 patients with pulmonary hypertension reported no procedure-related mortality (25). In contrast, a more recent survey of 202 pulmonary angiographies performed in patients with pulmonary hypertension reported three procedure-related fatal complications (26).…”
mentioning
confidence: 99%
“…1,5,7,8 However, in a population as fragile as PAH patients, there is often hesitance to perform invasive procedures such as catheterization, especially when it includes the use of GA. Much of this hesitation comes from anecdotal reporting and higher rates of mortality and serious complications from older series in the 1980s, 17,18 as there is very little recent literature regarding the risks and complication rates of catheterization in PAH patients. Hofmann et al 11 reported their 10-year single-center experience performing pulmonary angiography in 202 mostly adult patients with PAH in 2004 and found an overall complication rate of 2.0%, although all complications were major and 3 were fatal. In 2007, Taylor et al 12 reported their 5-year single-center experience performing catheterization under GA in 70 pediatric patients, finding an overall complication rate of 8.6%, a major complication rate of 5.7%, and 1 fatal outcome (1.4%).…”
Section: Discussionmentioning
confidence: 99%
“…[48] With the availability of new contrast agents and the use of selected views only, the pulmonary angiography has been shown to be safe in PH. [49] Pulmonary angiography can be part of the RHC but should be performed after all hemodynamic assessments have been performed.…”
Section: Clinical Approach To Pulmonary Hypertensionmentioning
confidence: 99%